2014
DOI: 10.1007/s00271-014-0448-y
|View full text |Cite
|
Sign up to set email alerts
|

The effects of container geometry on water and heat regimes in soilless culture: lettuce as a case study

Abstract: significantly with container height, especially for the high irrigation frequency treatments. Container geometry had an effect on the water and temperature regimes. Water content values in tall and narrow containers were lower than those in short and wide containers that had an equal volume of growth medium per unit length. Higher medium temperatures and daily fluctuations were observed in the tall containers. The calculated evapotranspiration rate was higher in the tall containers, and a stronger effect on ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
11
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 39 publications
4
11
1
Order By: Relevance
“…These results are partially similar to what Heller et al (2015) reported, on evaluating the effect of irrigations frequency and vessels geometry on lettuce, which had plants cultivated in smaller vessels with high irrigation frequency to present more leaves as non-commercial quality.…”
Section: Resultssupporting
confidence: 90%
“…These results are partially similar to what Heller et al (2015) reported, on evaluating the effect of irrigations frequency and vessels geometry on lettuce, which had plants cultivated in smaller vessels with high irrigation frequency to present more leaves as non-commercial quality.…”
Section: Resultssupporting
confidence: 90%
“…) thereby avoiding some of the complexities of changes in crop biomass allocation during the reproductive process (Heller et al. ). The study was conducted indoors using only artificial lighting, as this is the dominant approach found in most urban vertical farming projects, especially in plant factory designs (Kang et al.…”
Section: Introductionmentioning
confidence: 99%
“…The aim of this study was to compare a vertical column VFS and a conventional horizontal hydroponic system (HHS) with similar fertigation regimes, root zone volumes, and planting densities to determine whether VFS represents a viable alternative to HHS. Lettuce was used as a model plant as it is widely grown in hydroponics as a rapidly growing leafy vegetable (Safaei et al 2015) thereby avoiding some of the complexities of changes in crop biomass allocation during the reproductive process (Heller et al 2014). The study was conducted indoors using only artificial lighting, as this is the dominant approach found in most urban vertical farming projects, especially in plant factory designs (Kang et al 2014;He et al 2015) and allows more precise control of environmental conditions (Poorter et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Comparable conditions have been observed and described for potting containers at plant nurseries (Cassel and Neilsen, 1986; Handreck and Black, 2002; Heller et al, 2015) and for the maintenance of golf courses and sports fields (McCoy, 2014), but this hydraulic condition is not incorporated into most green roof models (Li and Babcock, 2014). Programs commonly used by design and engineering consultants, such as EPA‐SWMM (Rossman and Huber, 2015), treat the water holding capacity of a green roof medium as a fixed property throughout the profile.…”
mentioning
confidence: 99%